La motivación en el aprendizaje de Lengua y Literatura en los estudiantes de sexto grado “B”, escuela “Miguel Riofrío” de Loja, 2022-2023 - Loaiza Román, Dayana Madeley (2023)
The research, Motivation in learning, aims to analyze the incidence of Motivation in the learning of Language and Literature in sixth grade B students, Miguel Riofrío de Loja school, period 2022-2023. Three specific objectives were developed, the first was to identify the factors that affect the Motivation of students' learning in the subject of Language and Literature, the second was to design an educational proposal through motivation techniques to improve student learning, and the third was to evaluate the impact of the educational proposal of motivation techniques for the improvement of learning. To carry out this study, a type of descriptive research with a mixed approach was used, and its design was quasi-experimental. The inductive, deductive, analytical, and synthetic methods were applied during the process. In addition, the techniques that were used to carry out this research were direct observation, interview, survey, and evaluative evaluation. In the same way, the instruments used were the observation sheet, a questionnaire of structured questions, and a questionnaire. These contributed significantly to data collection. The research population was the "Miguel Riofrio" School of Basic Education, from which 21 students and one teacher were selected using a non-probabilistic sampling for convenience. It is important to mention that Motivation in learning is essential because it drives students' interest, participation, and effort, favoring better academic performance and meaningful learning. This was evidenced by the application of the didactic proposal, in which motivation techniques helped students develop attention and understanding of the knowledge imparted.